2022
DOI: 10.21203/rs.3.rs-1750069/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The utilization of health care services by people with type 2 diabetes living in slums in Tabriz, Iran, and sociodemographic factors that influence it: a cross-sectional study

Abstract: Background As one of the disadvantaged groups, slum-dwellers face health disparities. These disparities can also be attributed to inequalities in health care utilization. Therefore, this study aimed to investigate health care utilization among patients with type 2 diabetes living in Tabriz's slums in 2022. Methods A cross-sectional study was conducted. Our study included participants who were over 18 years old, did not suffer from physical and psychological disabilities and had lived in slums for at least 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The review revealed that individual, health system and contextual factors in uence type 2 diabetes management among slum dwellers. The review recommended that policymakers use the ndings to reduce barriers and augment facilitators of type 2 diabetes management among slum dwellers (34). A study conducted in 2023 explored barriers to health care utilization among patients with type 2 diabetes living in slums from the providers' perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review revealed that individual, health system and contextual factors in uence type 2 diabetes management among slum dwellers. The review recommended that policymakers use the ndings to reduce barriers and augment facilitators of type 2 diabetes management among slum dwellers (34). A study conducted in 2023 explored barriers to health care utilization among patients with type 2 diabetes living in slums from the providers' perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Self-e cacy was measured using the 10-item General Self-E cacy Scale (22), which assesses the perceived ability to cope with di cult demands in life on a 4-point Likert scale. The total score ranges from 10-40 points and is categorized as low (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), moderate (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), or high (31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Study Variablesmentioning
confidence: 99%